Detection of malachite green and leuco-malachite green in fishery industry - Ahmad Puat, Nurul Hidayah; Abu Bakar, Fatimah; Mahyudin, Nor Ainy; Salam, Faridah; Mohd Said, Nur Azura; Zaman, Muhammad Zukhrufuz (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
This article summarises the current methods for total malachite green (MG) detectionwhich is known as a sum of MG and leuco-malachite green (LMG) that has been used extensively in aquaculture as fungicide, dye color in textile and other purposes in food industries. LMG is a reducing form of MG, where the MG is easily reduced due to the photo-oxidative de-methylation process. Nevertheless, the use of MG had become an issue due to its toxicity effects. Many analytical instruments such as HPLC, LC-MS/MS, GC-MS, and spectrometry have been widely used for detection of MG. However, these methods require long time sample preparation and analysis, expensive, use hazardous reagents and indirect measurements. Hence, other analytical methods which are more sensitive, safe, rapid, inexpensive andportable are required. Alternatively, biosensors promise a more sensitive and rapid detection method for MG and LMG.